Photo-bioreactor structure and light-heat-mass transfer properties in photo-fermentative bio-hydrogen production system: A mini review. (27th April 2017) - Zhang, Zhiping; Zhou, Xuehua; Hu, Jianjun; Zhang, Tian; Zhu, Shengnan; Zhang, Quanguo
Abstract: Photo-fermentative bio-hydrogen production process is a complicated bio-chemical reaction process, its performance has a closely relationship with the configuration of photo-bioreactor, light distribution and density, generated heat from the bio-chemical reaction, and light-heat-mass transfer properties in the bio-hydrogen production system. Light and temperature have significant influence on the bacteria growth and enzyme activity, which further affects the performance of the photosynthetic bacteria and its hydrogen production potential. Current research status of the design of the photo-bioreactor, and transfer characteristics in the process of photo-fermentative bio-hydrogen production were reviewed in this paper. The design requirement, light distribution scheme, and heat-mass transfer enhancement approaches were all discussed. The in-depth understanding and grasp of the factors affecting light-heat-mass transfer performance in the hydrogen production process, effective regulation mechanism of photosynthetic hydrogen production can be put forward, and fundamentally optimized photo-fermentative bio-hydrogen production process, promoted the industrialization of biological hydrogen production process. Highlights: Photo-bioreactors with diverse configuration are listed. Light distribution and transmission properties in photo-fermentative bio-hydrogen production system are reviewed. Heat transfer properties inside the photo-bioreactor are discussed. Mass transfer properties and enhancement approaches are summarized. Relationship between bio-hydrogen production potential and bioreactor with diverse transfer properties are evaluated.